The Phenomenon of "Ijḥāf" in Morphological and Syntactic Studies: Concept and Application - Younis, Muhammad; Younis, Ahmad Saleh ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2015)
This study explores the phenomenon of Ijḥāf as it appears in classical morphological and syntactic scholarship, considering it a technical term with a notable presence in the Arabic linguistic tradition. The authors aim to examine this term in both its linguistic and terminological dimensions in order to define it precisely and clarify its connection to morphological and syntactic structures. The study adopts a descriptive-analytical approach to trace the term across classical linguistic sources, analyzing its usage and applications. The findings reveal that Ijḥāf carries a distinct semantic significance that links its lexical meaning with its functional role in morphological and syntactic contexts. This highlights the importance of re-evaluating certain traditional concepts with greater precision and theoretical grounding.